Volume 1: Advances in Control Design Methods; Advances in Nonlinear Control; Advances in Robotics; Assistive and Rehabilitation 2018
DOI: 10.1115/dscc2018-8977
|View full text |Cite
|
Sign up to set email alerts
|

Learning Based Speed Control of Soft Robotic Fish

Abstract: Bioinspired robotics takes advantage of biological systems in nature for morphology, action and perception to build advanced robots of compelling performance and wide application. This paper focuses on the design, modeling and control of a bioinspired robotic fish. The design utilizes a recently-developed artificial muscle named super coiled polymer for actuation and a soft material (silicone rubber) for building the robot body. The paper proposes a learning based speed control design approach for bioinspired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…SCP, a recently developed artificial muscle actuator, is lightweight, flexible, strong with a high power-toweight ratio and fabricated with silver-plated nylon threads (Yip and Niemeyer, 2017). Our study also showed through simulation that speed control of a one-dimensional robotic fish was successfully done with SCP actuators using reinforcement learning (Rajendran and Zhang, 2018;Sutton and Barto, 2018). Nevertheless, besides employing a sparsely discretized state space in the dynamics, our previous model is dimensionally limited which is too simplified to mimic the biological fish and study the swimming motion.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…SCP, a recently developed artificial muscle actuator, is lightweight, flexible, strong with a high power-toweight ratio and fabricated with silver-plated nylon threads (Yip and Niemeyer, 2017). Our study also showed through simulation that speed control of a one-dimensional robotic fish was successfully done with SCP actuators using reinforcement learning (Rajendran and Zhang, 2018;Sutton and Barto, 2018). Nevertheless, besides employing a sparsely discretized state space in the dynamics, our previous model is dimensionally limited which is too simplified to mimic the biological fish and study the swimming motion.…”
Section: Introductionmentioning
confidence: 56%
“…Following this, aiming towards a phased approach at developing reinforcement learning-based control for the soft robotic fish, a foundational Q-learning (Watkins and Dayan, 1992) based controller was designed and simulated to control the speed of a three-link robotic fish which consisted of discretized state and action spaces (Rajendran and Zhang, 2018). The robotic fish was restricted to one-dimensional locomotion and the agent was trained until the Frobenius norm between the current and previous Q-tables was minimized to a threshold.…”
Section: Preliminary Backgroundmentioning
confidence: 99%
See 3 more Smart Citations